Assessment of structural stormwater measures in Tehran through indicators of sustainable development - Ziller, Annette (2010)
This thesis suggests structural stormwater measures that should prevent negative impacts of stormwater evolved from Tehran´s drastic expansion. These measures should incorporate the concept of sustainable development in stormwater management. The study selects four structural sustainable stormwater measures appropriate for the 22nd district of Tehran. These are: extended detention basin, infiltration trench, sand filter and pervious pavement. The measures are assessed for their contribution to sustainable development in stormwater management in Tehran. In order to compare sustainable and conventional measures in respect to their contribution to sustainable development in stormwater management one conventional stormwater measure, a storm sewer, is also included. For the assessment one indicator set is developed that should describe the measures. The indicators are split into economic, environmental and social ones and thus represent the concept of sustainable development in stormwater management. By applying the scoring method final scores of the measures are gained. The final scores state to which extent each measure – relative to the other selected measures – incorporates the concept of sustainable development in stormwater management. One major finding is that a combination of extended detention basins and pervious pavement is proposed to tackle the problems due to stormwater in Tehran in a sustainable way.